Not-for-Profit Hospital CEO Performance and Pay: Some Evidence from Connecticut - Jeffrey Kramer; Rexford E. Santerre (SAGE Publishing, 2010)
This paper uses observations from a panel data set of 35 chief executive officers (CEOs) from 29 not-for-profit hospitals in Connecticut over the period 1998 to 2006 to investigate the relationship between CEO performance and pay. Both economic and charity performance measures are specified in the empirical model. The multiple regression results reveal that not-for-profit hospital CEOs, at least in Connecticut, are driven at the margin to increase the occupancy rate of privately insured patients at the expense of uncompensated care and public-pay patients. This type of behavior on the part of not-for-profit hospital CEOs calls into question the desirability of allowing these hospitals a tax exemption on earned income, property, and purchases.